Archive and Participatory Practices: Reflections on the South African Contribution in the Context of Documenta 15 - Francesca Zanella (piano b, 2025)
The Literature on participatory art practices today is characterized by a multiplicity of contributions that restores the complexity of an ongoing transformation characterized by a fragmentary nature of critical positions in the face of the growth of stories and practices. Since these practices are plural, on the one hand, and since the critical gaze has been dominated by the Western historical-critical tradition, it seems to us that today it is necessary to begin to take into account first of all how much the different contexts have characterized these practices. Precisely for these reasons, starting from a survey of the Reggio-Africa archive preserved in Reggio Emilia which testifies to the relations between the Emilian city and the southern African area since the 60s, South Africa has been identified as the territory of investigation. Dwelling above all on some experiences started at the beginning of the twenty-first century, and on collectives present at documenta 15, some questions will be asked with respect to the awareness and attention towards the archive which is the object and instrument of many participatory projects for its being intrinsically linked to the theme of memory, identity and history. Archive subject of participatory actions, but also a possible tool for their historicization.